The Effect of some Disinfectants on the Tensile Bond Strength of Tissue Conditioners to Acrylic Denture Bases (In Vitro Study) - جنيد, فادي; حيدر, حيدر (Latakia University Journal -Medical Sciences Series, 2020)
Tissue conditioners and disinfectants are most commonly used materials in prosthodontics. Caution should be taken while selecting the disinfectants which probably cause changes on properties of tissue conditioners. Aims of research: A comparative and evaluation effect of some disinfectants on the tensile bond strength of tissue conditioners to acrylic denture bases (in-vitro study). Materials and Methods: 400 rectangular samples of heat cure acrylic resin were made (30×10×3mm) with bevel in its end by 45°, (viscogel-GC) tissue conditioners were embedded between the acrylic blocks within a uniform mold with space 3mm. The solutions were used (sodium hypochlorite 5,25%, chlorhixidine 0,12% as disinfectants, distilled water as control group). Samples were divided into groups, and immersed in solutions every day for 5 minutes and tested during periods (before immersion, 24 hours, 7 and 15 days after immersion). Tensile bond strength was recorded with the universal testing machine at loading rate of 10mm\min. All samples were kept in distilled water in an incubator at 37°C. The solutions were changed daily. Data were analyzed using one -way ANOVA, T student SPSS 23, at p=0.05. Results: According to the results of this study, there were no significant statistical differences between disinfectant solutions and distilled water on the bonding strength of both of the two tested materials (p<0.05), as the averages of both materials tended to increase over time with significant statistical differences when comparing the mean differences, and the increase was higher with viscogel compared with GC.